MR of myelomatous meningitis. - Quint, D J; Levy, R; Krauss, J C (American Journal of Neuroradiology, 1995)
In a 56-year-old woman with multiple myeloma involving the leptomeninges diffusely, MR of the spine showed multiple vertebral compression fractures and marked enhancement of the cauda equina region. Intracranial MR showed pathologic enhancement of the left third and fifth cranial nerves.